A análise de assunto no processo de indexação: um percurso entre teoria e norma - Pozzi, Brisa; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2014)
Considered the step that constitutes the intellectual work of the indexer, the approach runs the focus of the initial phase of the indexing process - the subject analysis. Among the various denominations that can be achieved, the subject analysis reaches its dimension applied when observed the rules that underlie the indexing process. The release of the documentary information requires the development of contributions to aid in the procedures of analysis, synthesis and representation of the contents documentary, seeking contributions to both the theoretical sedimentation, and for fostering the professional practice of the librarian. Through bibliographic exploratory research, this article aims to contribute to the relevance of subject analysis, concluding that there is a gap in the use of NBR 12676/1992, as well as the need for its updating.

Considerada a etapa que constitui o trabalho intelectual do indexador, o foco nesse ensaio percorre a abordagem da fase inicial do processo de indexação, denominada análise de assunto. Entre as várias denominações que pode alcançar, a análise de assunto atinge sua dimensão aplicada quando observada as normas que embasam o processo de indexação. A disponibilização da informação documentária necessita do desenvolvimento de aportes que auxiliem nos procedimentos de análise, síntese e representação do conteúdo documentário, buscando contribuições tanto para a sedimentação teórica, quanto para fomentar a prática profissional do bibliotecário. Por meio da investigação exploratória bibliográfica, este artigo visa contribuir para a relevância coberta pela análise de assunto, concluindo que existe uma lacuna na utilização da NBR 12676/1992, como também a necessidade de sua atualização.
Analysis of topic in case of index: a journey between theory and standard
Keywords: análise de assunto; indexação